Peran Work-Life Balance: Hubungan Antara Otonomi Kerja dan Keterlibatan Kerja Pada Pendidikan Tinggi di Indonesia - M Halim; Yuni Siswanti; Tiara Juniar Soewardi; Aldini Nofta Martini Martini (General Multidisciplinary Research Journal, 2025)
Introduction: This study extends previous research that uncovers the relationship between job autonomy and work engagement, and examines the mediating effect of work-life balance on lecturers in Indonesian higher education. Methods: We collected research data using an online survey of lecturers in Indonesian higher education, and analyzed the data. Results: As a result of the research data analysis, we found that there is a mediating effect of work-life balance. Conclusion and suggestion: As a result of the research data analysis, we found that there is a mediating effect of work-life balance. Future studies should analyze samples from different countries with different cultures and institutions to compare the results or use these variables as control variables. It is necessary to include different types of companies in the sample or to examine whether there are differences in the results of the study depending on the size of the company or industry.